Assessment of Nurses' Practices Toward Infection Control Standardized Precautions in Azady Teaching Hospital in the City of Kirkuk - mahmud, Nazar; Abdul Sahib, sanaa (Iraqi National Journal of Nursing Specialties, 2011)
Objective: The aim of the present study is to assess the practices of nurses towards standard precautions at AzadyTeaching Hospital in the City of Kirkuk.Methodology: A descriptive study, which uses the assessment approach and it was conducted on nurses from January18th, 2009 to September 30th, 2009, using non-probability sampling a purposive sample of (37) subject (male andfemale nurses) who worked at surgical wards in Azady Teaching Hospital in Kirkuk city was selected. Two studyinstruments were utilized for proper data collection [questionnaire and observational checklist]; a questionnaire wasdeveloped for the purpose of the study. It was comprised of two parts which included the nurses' demographiccharacteristics and Information related to the setting of the sample (surgical wards). A pilot study was carried out forthe period of January 18th, 2009, to February 2nd, 2009 to determine the observaƟonal checklist reliability throughthe use of (Inter–rater). A panel of (19) experts was involved in the determinaƟon of the observaƟonal checklistcontent validity. Data were analyzed through the application of descriptive statistical data analysis approach(frequency, percentage, mean of scores and standard deviation), and inferential data analysis approach (chi-square).Results: The study findings revealed that the majority (91.9%) of the nurses did not get training sessions regardinginfecƟon control and (83.4%) of them had not parƟcipated conƟnuous learning about infecƟon control. According tothe level of practices towards standard precautions, it has revealed that poor practices of standard precautions bysurgical wards nurses had shown in surgical wards.Recommendations: The study recommended that special education programs can be designed and presented to thesurgical ward nurses and to all the hospital staff in order to increase their awareness towards infection.